ANALISIS RISIKO KEUANGAN PADA PERUSAHAAN DI ERA KETIDAKPASTIAN EKONOMI GLOBAL: FOKUS PADA RISIKO LIKUIDITAS DAN RISIKO KREDIT - Hanifa Salsabila; Sri Adel Febri Aldina; Ricky widyanto; Pinastika Alya Disti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article analyzes the financial risks faced by companies in the era of global economic uncertainty, focusing on liquidity risk and credit risk. In the context of a volatile economy, companies are often affected by various external factors that can disrupt their financial stability. Liquidity risk refers to a company’s ability to meet short-term financial obligations, while credit risk relates to the likelihood of debtor default. This research employs qualitative and quantitative analysis methods to evaluate the impact of these two types of risk on the financial health of companies. The analysis results indicate that companies lacking adequate risk management strategies tend to struggle in maintaining healthy cash flows, which can lead to increased borrowing costs. Moreover, global economic uncertainty, including interest rate changes and exchange rate fluctuations, exacerbates companies’ exposure to these risks. This article suggests that companies conduct regular risk assessments and implement effective mitigation policies to reduce the impact of liquidity and credit risks.By doing so, companies can be better prepared to face challenges arising from uncertain economic conditions.